2012
DOI: 10.4028/www.scientific.net/kem.509.26
|View full text |Cite
|
Sign up to set email alerts
|

Improvement on the Crack Resistance Property of Semi-Flexible Pavement by Cement-Emulsified Asphalt Mortar

Abstract: Semi-flexible pavement (SFP) has some excellent characteristic such as high carrying capacity, good wearing resistance, water stability and durability. However, the SFP appears low temperature crack and fatigue cracking seriously because there are large differences in the interfacial bonding property and the elastic modules between its two major parts: Lag gap asphalt mixture (LGAM) and cement mortar. All of these are caused by the large stiffness of cement mortar. In order to improve the crack resistance prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Studies by Hao and Ling [12,13] indicated that semi-flexible pavement have good low temperature cracking resistance and excellent rutting resistance. Huang et al [14] used six emulsified asphalt-to-cement (A/C) ratios and found 0.3 was the optimum one that can balance performance of SFCM between elastic modulus and fatigue life [14]. Al-Qadi et al [2,6] studied SFCM as a possible alternative for bridge deck overlays considering its improved engineering performance compared to a typical AC wearing surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Hao and Ling [12,13] indicated that semi-flexible pavement have good low temperature cracking resistance and excellent rutting resistance. Huang et al [14] used six emulsified asphalt-to-cement (A/C) ratios and found 0.3 was the optimum one that can balance performance of SFCM between elastic modulus and fatigue life [14]. Al-Qadi et al [2,6] studied SFCM as a possible alternative for bridge deck overlays considering its improved engineering performance compared to a typical AC wearing surface.…”
Section: Introductionmentioning
confidence: 99%
“…The skid resistance of SFCM was noted as a problem shortly after paving but it was improved within a few months, and kept at a good level by the end of the fourth year. The pavement condition rating (PCR) value of SFCM, which is a parameter to quantify pavement's overall performance based on measurements of roughness, surface distress, skid resistance and deflection, were acceptable by the end of the survey [14].…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Wu [8] evaluated the cracking resistance of semiflexible pavement materials based on the fracture toughness using the J-integral theory and three-point bending semicircular beam test. Huang et al [9] studied the cracking resistance of semiflexible pavement materials based on cement-emulsified asphalt mortar. At present, studies of the anticracking of semiflexible pavement have been mainly focused on controlling the volumetric stability of the cement mortar and the overall cracking resistance of semiflexible pavement materials.…”
Section: Introductionmentioning
confidence: 99%
“…(1) SFCM is the combination of the open-graded asphalt mixture (as the core structure) and cement mortar (as the filler). It combines the flexibility and durability of the asphalt concrete and the stiffness of the cement concrete (9,18).…”
mentioning
confidence: 99%
“…They focus on either modifying the track component or making changes to the entire structure. Amplifying the size and/or increasing the space between the ties is a simple method of modifying the track component, which could reduce the vertical displacement by distributing the loads to a broader area ( 8 , 9 ). Rubber pads are often used in the railway to reduce vibration and improve the damping of the structure ( 10 ).…”
mentioning
confidence: 99%